Vegetation Analysis of Tarsius Habitat (Tarsius Sp.) in Panua Nature Reserve, Pohuwato Regency, Gorontalo Province - Nurma Rosalia; Feri Novriyal; Dewi Wahyuni K. Baderan; Ramli Utina (Universitas Muhammadiyah Palu, 2024)
The research aims to analyze the vegetation habitat of Tarsius (Tarsius sp.) in the Panua Nature Reserve, Pohuwato Regency, which will be carried out in April-June 2023. The research location is in the Panua Nature Reserve, Marisa District, Pohuwato Regency, Gorontalo Province. Data collection at tarsier nest locations was divided into 3 stations, namely Station 1 was in a secondary forest location, station 2 was at the border location of secondary forest and plantations, and station 3 was at a plantation location. Collecting plant data by plot and analyzing the importance value for each type of plant. The results obtained were that there were 55 types of plants in the Tarsius (Tarsius sp) habitat in the Panua CA landscape, which were distributed in 3 areas, namely primary forest areas, border areas and plantation areas (secondary forests). Bamboo plants and sugar palm plants were used as Tarsius nests at station 1, Rattan plants and Ficus sp plants were used as Tarsius nests at station 2, while at station 3 the plants used as nests were bamboo plants, Nantu plants and rattan plants.Keywords: Tarsius, Tarsius Nest, Panua Nature Reserve, Bamboo, Rattan